"Style that leaves nothing to be desired": Whanganui’s Ladies Club of 1897 - Flutey, Scott (Architectural History Aotearoa, 2023)
In 1897, a new, purpose-built institution made national headlines when it opened in the colony’s fifth-largest centre. The Wanganui Ladies’ Club was marketed as the first and only club of its kind, and was based on a Gentlemen’s Club model catering to the upper classes of town and country. Designed by local architect William Pinches, a public tea room allowed non-members access to part of the building and much was made of its points of difference. In the immediate wake of women’s suffrage being granted, proprietor Harriet Cameron was riding the crest of a wave of local women leading new, public-oriented lives. Described as artistic and luxurious, the interior was perhaps the most lavishly decorated in town. Photographs of it were widely published and the Ladies’ Club seemed poised to become a fashionable social and political hub of the district. Yet within five years the club had dissolved, and the building would be lost only twenty-five years later. Its demolition reflected a wider shift in values and aesthetics, and the declining influence of the British-modelled established gentry over the region’s cultural life. This paper will visit the interior of the lost Ladies’ Club through sharing recent research on the building. It will examine a few contemporary local 1890s interiors which have survived, and look at high society club culture which has survived in the town against the odds.